Ethical Aspect of a Contemporary Enterprise: Empirical Evidence from Poland - Irena DUDZIK-LEWICKA (Communications of International Proceedings, 2022)
The following artcile is devoted to an important contemporary issue, referring to ethical creation of a long-lasting business strategy. The material gathered has made it possible to analyze the key problem through empirical studies. The main goal is to find out whether in contemporary entrepreneurs’ opinion there is a place for ethics in business, and if they are inclined to build their business strategy based on ethical principles. Having analyzed the results obtained through the conducted research, a main conclusion has been reached that Polish entrepreneurs have not incorporated much ethics into their business yet and are not conscious of its role, as they have not acknowledged the full meaning of this tool.
Keywords: ethics; business; values; strategy; Poland; enterprise behaviour